MO212LATE EVIDENCE OF SARS-COV-2 INFECTION IN A PATIENT WITH ACUTE KIDNEY INJURY (AKI) AND MASSIVE DEEP VEIN THROMBOSIS (DVT) STARTING FROM A HEMODIALYSIS CENTRAL VENOUS CATHETER (CVC). (29th May 2021) - Di Vico, Deborah; Cersosimo, Katia; Fofi, Claudia; Moioli, Alessandra; Tipaldi, Marcello Andrea; Grossi, Stefano; Mene', Paolo
Abstract: Background and Aims: COVID-19 has heterogeneous clinical manifestations. SARS-CoV-2 related AKI and hypercoagulability are negative prognostic factors. The incidence of thromboembolic events is about 30%, of AKI up to 20%. We report a patient with severe AKI who required hemodialysis (HD) and developed a massive DVT developing from the femoral CVC, and belatedly testing positive for SARS-CoV-2 in the absence of typical pulmonary involvement. Method: A 53-year-old male with a clinical history of hypertension, type II diabetes mellitus, in therapy with metformin and ace-inhibitor, was admitted to our E.R. with diarrhea, nausea and vomiting for about 2 days. Main signs: ideomotor slowdown, mild hypohydration and reduced urine output (unrelevant sediment). Initial blood tests showed severe AKI with hyperkalemic metabolic acidosis and hyponatremia (sCreatinine 18.76 mg/dl, BUN 161 mg/dl, K+ 7.8 mmol/l, Na+ 128 mmol/L, HCO3- 9.8 mmol/l). Mild neutrophilic leukocytosis with lymphopenia was detected, with slightly increased inflammation indices (CRP 1.05 mg / dl, D-dimer 720 ng / ml). CT scan: absence of typical SARS-CoV-2 signs, normal kidneys, no dilation of urinary tract. SARS-CoV-2 rapid antigen test and the first molecular swab test were negative. After femoral CVC insertion, HD was needed for a few sessions. Broad range antibiotic therapy was also set. On Day 3: a second SARS-CoV-2 PCR swab test resulted negative. He never manifested fever or dyspnea. On Day 6, despite an improvement of renal function (sCr 2.7 mg/dl), the patient, although he walked, presented right leg pain with signs of DVT. Ultrasound and angio-CT scan documented peri-catheter DVT extended to the common femoral and external iliac vein and superficial femoral vein involvement, without pulmonary embolism. I.v. therapy with sodium heparin was therefore started with quite a difficulty in reaching the expected range. On day 8, massive flittene appeared, the CVC was removed and a caval filter was placed; marked neutrophilic leucocytosis and increased inflammatory indices (CRP 11.50 mg/dl) was documented. Nevertheless, thrombosis has progressed to the entire venous axis and the inferior cava. Through a tibial vein introducer local i.v. alteplase was also started. Just after, copious bleeding from the site of the removed CVC followed by haemorrhagic shock occurred and the patient was transferred to the ICU (D-dimer 219800 ng/ml). The same day a third swab for SARS-CoV-2 resulted positive while a further CT-scan did not show signs of virus-like interstitial pneumonia. On the following day (day 9) the patient underwent thrombus aspiration (Aspirex®S device) and fasciotomy of the right leg for a compartment syndrome. Results: Despite the continuation of heparin, PTT ratio was never >1.5, with an extension of DVT and also involvement of the contralateral iliac vein, as well as a worsening of the clinical-laboratory picture and patient's death on day 14. Serum complement, autoantibodies (ANA, ANCA, ENA, ANTI-dsDNA, anti-cardiolipin, AMA, anti-B-glycoprotein) and factor V Leiden test were normal. All blood cultures were found to be sterile. Conclusion: Our case confirms the heterogenicity of COVID-19 manifestations, often without pulmonary involvement. According to our experience from the onset of the pandemic, SARS-CoV-2 can also be found later in patients with already advanced organ damage. In this case, in the absence of other possible factors, AKI and intestinal involvement may have been early signs of COVID-19, with a virus initially not detectable in the nasopharyngeal mucosa. Furthermore, the increased thromboembolic risk of COVID-19 should not be underestimated in the presence of risk factors as external devices, also given the difficult management of anticoagulation target. Anticoagulant prophylaxis in cases with doubtful symptomatology and CVC must be considered even in non-bedridden patients, due to the current risk of SARS-CoV-2 infection.